Stable isotope and fatty acid compositions of monovarietal olive oils: Implications of ripening stage and climate effects as determinants in traceability studies. (November 2015) - Portarena, S.; Farinelli, D.; Lauteri, M.; Famiani, F.; Esti, M.; Brugnoli, E.
Abstract: The quantitative variability of isotopic and fatty acid compositions in extra virgin olive oil was investigated in relation to variety, olive ripeness index and geographical origin. The study was carried out in two environments of Umbria region (central Italy), differing in annual/seasonal temperatures and rainfalls. Significant correlation was found between oil isotope compositions and climatic seasonal changes during fruit ripening. Moreover, significant isotopic differences among cultivars were related to the period of maximum oil accumulation in the fruits and to the fatty acid profile. A carbon kinetic isotopic effect could be associated with the fatty acid elongation from palmitic to stearic acid and to the unsaturation step leading from oleic to linoleic. No correlation was found between stable isotope and fatty acid compositions during fruit ripening. The analyzed cultivar and ripening effects on oil traceability issues are discussed in order to focus the resolution power of stable isotope methodologies and the possibility to distinguish monovarietal oils from the same area. Highlights: We analyzed δ 13 C and δ 18 O of monovarietal oils collected at different ripenings. Isotope ratios correlate with climatic seasonal changes during fruit ripening. Isotope values, oil accumulation pattern and fatty acids profile were correlated. Perspectives of stable isotopes technologies in traceability studies are discussed.